Understanding the effect of social media marketing activity for promoting intention to participate in martial arts - Xie, Ming-Chuan; Chang, Yao-Chuan; Cai, Chuan-Ming (Frontiers in Psychology, 2022)
The development of folk martial arts in China has encountered many obstacles and difficulties in promoting the sport. Although there are many martial arts-related groups on WeChat, the largest social media in China, the interaction is not enthusiastic enough and the participation is too low. The main purpose of this study is to understand the impact of social media marketing activities and user experience on the intention of people to participate in martial arts through a quantitative research method. After the literature study, a research model was developed based on Theory of Planned Behavior (TPB), in which the constructs include social media marketing activities, user experience, attitudes toward martial arts, subjective norms, martial arts attachment, and participation intention. The results of the study illustrated that social media marketing activities and user experience had a positive and significant effect on martial arts attitudes, subjective norms, and martial arts attachment via Structural Equation Modeling (SEM). Martial arts attitudes, subjective norms, and martial arts attachment had a positive and significant effect on the intention to participate. Finally, based on the results of this study, we propose suggestions for social media marketing activities, user experience, martial arts attachment, attitudes toward martial arts, subjective norms, and martial arts participation intentions for martial arts social media operators, martial arts promotion organizations, and subsequent studies.